Natural Moisturizer Based Formulation of Green Leaf Jelly (Cyclea Barbata Miers) with Bengkoang Addition (Pachyrhizus Erosus) - Muhammad Ilham; Kun Harismah; Ahmad Mubarok; Santi Harianti (Jurnal Dedikasi, 2020)
The earth is getting hotter due to the increasingly intense sun exposure. Because of that the sun's rays will look bad for humans, especially on human skin. This sun exposure can cause various problems, especially on the skin, such as dry skin. One way to overcome this problem is to use skin moisturizers regularly. Various types of skin moisturizers have been widely circulating in the market, but many people are not suitable to use these items because of many things. Natural moisturizers can be the solution. Formulations of green grass jelly and bengkoang leaves can be an alternative use of natural moisturizers. One of the ingredients in green grass jelly leaves is the content of polyphenols and flavonoids contained in green grass jelly leaves can function as antioxidants. Antioxidants can fight free radicals in the body. Whereas in yam, one of the substances that exist is Flavonoid is a natural sunscreen to prevent skin damage due to free radicals and phenolic substances effective to inhibit the process of formation of melanin bengkoang useful as a natural skin lightener. Based on SNI-16-4399-1996, all samples that have been made meet the existing standards and the formulation samples that comply with the standard are F (D), ie green grass jelly concentration of 2.5% and  Bengkong 5%